PENGARUH PERMAINAN PLASTISIN TERHADAP PERKEMBANGAN KEMAMPUAN MOTORIK HALUS ANAK USIA PRASEKOLAH DI TK SWASTA KARUNIA MEDAN JOHOR - Tarigan, Herri Novita (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2023)
The golden time is frequently used to describe children in the pre-school years. Children's intelligence is now growing and developing extremely quickly, as are their fine and gross motor skills, cognition, morals, social skills, emotional development, and linguistic skills. Writing and sketching by pupils that are not tidy, gripping things that frequently fall, and stiff finger motions are all issues with the fine motor development of preschoolers. The purpose of this study was to analyzing the effect of plasticine games on the development of fine motor ability in preschool children. The type of this study was quasy experiment using one group pretest-posttest. The population in this study were all students of Karunia Private Kindergarten, Medan, Johor. The number of respondents in this study were 26 respondents taken with total sampling. The results of the bivariate analysis of playing plasticine to development of fine motor skills in pre-school children obtained p-value (sig 2 tailed) = 0.000. From the results of the bivariate analysis p-value < a (0.05), it can be concluded that there is an effect of playing plasticine to development of fine motor skills of pre-school-aged children in Karunia Private Kindergarten, Medan Johor in 2023. To ensure that children develop to their full potential, it is intended that parents and kindergarten instructors would actively participate in stimulating children's development activities.